Techniques For Forming a Winter Garden - N. V. Drobchenko; G. N. Djuraeva (Genius Journals, 2023)
The winter garden is an evergreen corner of nature in the house. The inner composition of the winter garden is connected with the outer space of nature. Comfort and beauty are emphasized by plants combined together with interior items into a beautiful green oasis. The article discusses the types of winter gardens, design features and selection of plants.
Keywords: glass structures; residential winter garden; greenhouse